Back Cover: Low‐thermal‐conductivity group 13 chalcogenides as high‐efficiency thermoelectric materials (Phys. Status Solidi A 1/2013). Issue 1 (15th January 2013) - Kurosaki, Ken; Yamanaka, Shinsuke
<x xml:space="preserve">Abstract</x> The low efficiency of thermoelectric (TE) materials in converting heat to electricity is the main impediment to applying TE generators in many industries. To enhance the efficiency of TE materials, quantified by the figure of merit ZT, it is important to reduce the lattice thermal conductivity of a material while maintaining a high electrical conductivity. In their Feature Article on pp. 82–88, Kurosaki and Yamanaka review the TE properties of chalcogenides containing elements from group 13, particularly compounds with crystal structures derived from the diamond structure, such as the zinc‐blende and the chalcopyrite structures. As shown on the cover, Ga2Se3 with point vacancies clearly has a higher thermal conductivity than Ga2Se3 with in‐plane vacancies. The presence of vacancies alone does not result in effective phonon scattering; rather, vacancies should form an in‐plane defect structure to realize effective phonon scattering. Introducing structural vacancies with in‐plane defect structures is a promising new method for reducing the thermal conductivity of thermoelectric materials and increasing the figure of merit ZT. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>